2005
DOI: 10.1093/pubmed/fdi055
|View full text |Cite
|
Sign up to set email alerts
|

Women with learning disability and uptake of screening: audit of screening uptake before and after one to one counselling

Abstract: Although the uptake of breast screening was found to be good, cervical screening uptake for women with learning disability was low and remained low after a supportive intervention designed to increase uptake. The greater acceptability of breast screening in women with moderate to severe learning disability compared to cervical screening has been confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 5 publications
2
37
0
Order By: Relevance
“…It was evident that participants often contributed to a cost-benefit analysis during which the benefits of carrying out screening were balanced against the potential for distress as part of best interest decisions and, consistent with previous research (e.g. Biswas et al, 2005), that decisions not to proceed with screening are appropriate in some circumstances.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It was evident that participants often contributed to a cost-benefit analysis during which the benefits of carrying out screening were balanced against the potential for distress as part of best interest decisions and, consistent with previous research (e.g. Biswas et al, 2005), that decisions not to proceed with screening are appropriate in some circumstances.…”
Section: Discussionsupporting
confidence: 75%
“…Studies designed to improve the uptake of cervical screening by women with intellectual disabilities using learning disability nurse interventions have demonstrated some improvement; however this research also suggests that cervical screening may not be considered in the best interest of some women on the basis of their established lifestyle behaviours and low risk status (Wilkins, 2004;Biswas, Whalley, Foster et al, 2005). Watts (2008) in a review of the literature argued that there was 'a notable gap in the research literature of fully reported empirical studies investigating factors that prevent women with intellectual disabilities from accessing cervical screening' (p. 524).…”
Section: Introductionmentioning
confidence: 99%
“…; Biswas et al . ; Gesualdi ; Lalor & Redmond ). This is an important limitation, as we can speculate that persons receiving IDD services are likely to be more frequently oriented towards appropriate health care than those unknown to IDD services.…”
Section: Introductionmentioning
confidence: 99%
“…In this group, 48 were eligible for breast screening and 37 (77%) had attended. Although the figures for breast screening were high, mammography up-take accounted only for those in contact with learning disability services (28).…”
Section: Up-take Of Mammography Screening In Women With Ds and Other mentioning
confidence: 98%
“…Another British study undertook an audit of women with moderate to severe learning disabilities aged 20-64 years in contact with NHS learning disability services (28). Among 235 eligible women known to the service, only 160 were traceable.…”
Section: Up-take Of Mammography Screening In Women With Ds and Other mentioning
confidence: 99%